Bridging Reading and Speaking for Developing Academic Presentations among Undergraduates - Lasanthi, K.; Paranthaman, V. (Faculty of Arts University of Jaffna, Sri Lanka, 2025)
This study investigates the integration of reading and speaking skills as a means of enhancing academic presentations among undergraduate students. Academic presentations play a vital role in university education, contributing to students’ communicative competence and preparing them for future professional contexts. Despite their importance, many undergraduates encounter challenges such as limited subject knowledge, inadequate content mastery, disorganization, and low confidence, all of which negatively affect presentation performance. The primary aim of this research is to examine these challenges and identify their underlying causes. Specifically, the study seeks to assess the impact of reading and speaking skills on presentation effectiveness and to propose practical strategies for addressing the difficulties faced by students. A mixed-methods approach was adopted, combining quantitative and qualitative techniques. Data were collected through Google Forms administered to the undergraduate students and semi-structured interviews with the lecturers, who provided insights into common deficiencies observed during student presentations. Pre-tests and post-tests were also employed to evaluate the effectiveness of integrating reading and speaking skills. The findings indicate that insufficient subject knowledge and weak content mastery constitute major barriers to effective presentations. Additionally, lack of organization and low self-confidence further hinder performance. However, the integration of reading and speaking skills was found to significantly improve comprehension, critical thinking, and audience engagement, resulting in more effective and impactful presentations. The study highlights the essential role of academic presentations in developing key skills such as public speaking, critical thinking, and effective communication. It concludes that incorporating reading and speaking skill integration into the undergraduate curriculum can enhance students’ confidence and presentation quality. The outcomes of this research are expected to benefit both educators and learners by refining teaching methodologies and enriching the learning experience, ultimately producing competent presenters who are wellprepared for academic and professional challenges.
Keywords: Academic presentations; Reading skill; Speaking skill; Skill integration